The Approximations of the Exact Boundary Condition at an Artificial Boundary for Linearized Incompressible Viscous Flows (Journal of Computational Mathematics, 1998)
We consider the linearized incompressible Navier-Stokes (Oseen) equations in a flat channel. A sequence of approximations to the exact boundary condition at an artificial boundary is derived. Then the original problem is reduced to a boundary value problem in a bounded domain, which is well-posed. A finite element approximation on the bounded domain is given, furthermore, the error estimate of the finite element approximation is obtained. Numerical example shows that our artificial boundary conditions are very effective.
Keywords: Oseen equations; Artificial boundary; Artificial boundary condition; Finite element approximation; Error estimate.